2021
DOI: 10.3390/vaccines9111322
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Sex and Gender Reporting in COVID-19 Clinical Trials

Abstract: Sex and gender have implications for COVID-19 vaccine efficacy and adverse effects from the vaccine. As vaccination is one of the key responses to the COVID-19 pandemic, it is vital that sex and gender differences be acknowledged, measured, and analysed in clinical research. Here, we systematically review published COVID-19 vaccine trials, both interventional and observational, to assess the quality of reporting of sex and gender. Of the 75 clinical trials on COVID-19 vaccines included in this review, only 24%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 49 publications
8
45
0
1
Order By: Relevance
“…In another study of an inactivated virus COVID-19 vaccine (Sinovac COVID- 19), the frequency of adverse events was higher among female medical staff [13]. In a recent study on the 75 clinical trials on different types of COVID-19 vaccines, 24% reported their main results disaggregated by gender, and only 13% mentioned the implications of their study for females and males [14]. In a mini review of studies reporting safety outcomes of COVID-19 vaccines, the authors found a significant lack of gender-disaggregated evidence across studies [15].…”
Section: Introductionmentioning
confidence: 99%
“…In another study of an inactivated virus COVID-19 vaccine (Sinovac COVID- 19), the frequency of adverse events was higher among female medical staff [13]. In a recent study on the 75 clinical trials on different types of COVID-19 vaccines, 24% reported their main results disaggregated by gender, and only 13% mentioned the implications of their study for females and males [14]. In a mini review of studies reporting safety outcomes of COVID-19 vaccines, the authors found a significant lack of gender-disaggregated evidence across studies [15].…”
Section: Introductionmentioning
confidence: 99%
“…Multivariable logistic regression analysis was performed to identify the factors related to vaccine hesitancy. Variables in the multivariate analysis were selected among factors exhibiting statistical significance in the univariate analysis and factors reported to be associated with vaccine hesitancy: sex, age at enrollment, disease duration, living with older individuals, use of immunomodulators and use of vedolizumab [ 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In the multivariable analysis, age (OR: 0.96, 95% CI: 0.92–1.00, p = 0.042) and the use of immunomodulators (OR: 0.08, 95% CI: 0.01–0.66, p = 0.019) was significantly associated with vaccine hesitancy ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire included questions regarding the patient’s demographic data (sex, age at recruitment, and age at disease diagnosis), epidemiological history of COVID-19, gastrointestinal symptoms, current medication use, history of COVID-19 vaccination, intention to be vaccinated against COVID-19, and reasons for acceptance or refusal of such vaccination ( Table S1 ). Additionally, the questionnaire included questions about factors that have been reported to be associated with COVID-19 vaccination hesitancy, such as cohabitation status, smoking status, and comorbidities [ 5 , 8 , 9 , 10 , 11 , 12 ]. After providing online consent, participants completed several questionnaires using the secure Research Electronic Data Capture (REDCap) platform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overwhelming amount of evidence indicates that COVID-19 has considerable sex and gender disparities in conjunction with infections, hospitalizations, and mortalities [ 76 , 77 ]. Initially, COVID-19 infections were thought to have similar susceptibility to both men and women; however, clinical findings, connecting severity and fatality, are strikingly higher in males than females [ 78 , 79 ], which could be due to distinctions of male vs. female adaptive and innate immune responses, hormonal differences, social/behavioral habits, and comorbidities ( Figure 4 ).…”
Section: Sex and Gender Differences And Their Relevance To Covid-19mentioning
confidence: 99%